PENGARUH PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM - Mohammad Zidny Khoiron; Edwin Agus Buniarto; Erwin Syahputra; Ahmad Maulana (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This study aims to determine the effect of profitability and dividend policy on stock price studies in food and beverage companies on the Indonesia Stock Exchange in 2011-2016. In this study profitability was measured using Basic Earning Power (BEP) dividend policy using Dividend Payout Ratio (DPR) and stock prices using the closing price (Closing price). The population in this study were all food and beverage companies listed on the Indonesia Stock Exchange in 2011-2016, while the samples in this study were food and beverage companies that met the research criteria so that as many as 6 companies were obtained by using purposive sampling technique. Data analysis was performed using multiple linear regression models. The results of the study stated that Basic Earning Power (BEP) and Dividend Payout Ratio (DPR) had a significant positive effect on stock prices. This means that Basic Earning Power (BEP) and Dividend Payout Ratio (DPR) have a relationship with stock prices, so the two ratios are also one aspect that needs to be taken into account when investing in shares.